(untitled) - Lundblad, Roger L. (Boca Raton, 2007)
The only current collection of its kind, Biochemistry and Molecular Biology Compendium provides a list of acronyms with definitions as well as a glossary of terms and subjects for systems and techniques used in biochemistry, molecular biology, biotechnology, proteomics, genomics, and systems biology. It also covers the 100 most frequently used chemicals, including those contained in commercial mixtures such as protease inhibitor cocktails, and the most frequently used base media for fermentation and cell culture. This text offers comprehensive information for the validation of biotechnology assays and manufacturing processes along with a compendium of commonly used analytical procedures.
Keywords: Biochemistry,Molecular biology,Hóa sinh,Sinh học phân tử